2007
DOI: 10.1063/1.2746058
|View full text |Cite
|
Sign up to set email alerts
|

Leakage currents at crystallites in ZrAlxOy thin films measured by conductive atomic-force microscopy

Abstract: Articles you may be interested inLocal charge transport in nanoscale amorphous and crystalline regions of high-k ( Zr 0 2 ) 0.8 ( Al 2 O 3 ) 0.2 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…[3][4][5][6][7] Conductive atomic force microscopy ͑CAFM͒ has been widely used to evaluate the electrical conduction of polycrystalline high-k dielectrics. Whereas some studies have suggested that conduction through the polycrystalline films occurs primarily through the bulk of the grains, 8,9 others have demonstrated that the leakage current flows preferentially through the grain boundaries ͑GBs͒, 3,7,10,11 which agrees with the results of ab initio calculations. 12 Besides generally expected differences associated with the intrinsic properties of the studied materials, such a discrepancy could be caused by the limits of the CAFM lateral resolution, which are close to the characteristic GB width.…”
supporting
confidence: 70%
“…[3][4][5][6][7] Conductive atomic force microscopy ͑CAFM͒ has been widely used to evaluate the electrical conduction of polycrystalline high-k dielectrics. Whereas some studies have suggested that conduction through the polycrystalline films occurs primarily through the bulk of the grains, 8,9 others have demonstrated that the leakage current flows preferentially through the grain boundaries ͑GBs͒, 3,7,10,11 which agrees with the results of ab initio calculations. 12 Besides generally expected differences associated with the intrinsic properties of the studied materials, such a discrepancy could be caused by the limits of the CAFM lateral resolution, which are close to the characteristic GB width.…”
supporting
confidence: 70%
“…2016) leakage current path in crystalline dielectrics. 16 Additionally the breakdown field of the laminated films is increased, which further improves the reliability of the layers. This reliability improvement becomes obvious, when evaluating the switching endurance of the layers (FIG.…”
Section: Resultsmentioning
confidence: 99%
“…The leakage currents are comparable to amorphous samples. The grain boundaries as main leakage paths 16,17 of these crystallites are passivated by the amorphous matrix, as it has been proposed for other crystallites by Heitmann et al 18 With a CaTiO 3 thickness above 30 nm, the number of crystallites increases significantly (Fig. 3).…”
mentioning
confidence: 86%
“…This leads to a much higher number of leakages paths along grain boundaries. 16,17 As a result, with oxide thicknesses greater than 30 nm, leakage current increases significantly (see TAT in Fig. 1(b)).…”
mentioning
confidence: 92%